2021
DOI: 10.1002/apj.2736
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient catalytic transfer hydrogenation of 5‐hydroxymethylfurfural to 2,5‐dimethylfuran over CuxZnAl catalysts

Abstract: Transformation of biomass-based feedstocks to fuels or valuable chemicals is of great importance to reduce our reliance on fossil resources. In this work, 2,5-dimethylfuran (DMF) production through catalytic transfer hydrogenation of 5-hydroxymethylfurfural (5-HMF) in liquid phase was investigated over ternary Cu x ZnAl catalysts using isopropanol as hydrogen donor. The excellent catalytic performance of the Cu x ZnAl catalysts can be attributed to the welldispersed Cu species with optimal proportions of Cu 2+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The analysis of pH effects on the conversion of HMF to various reduction products led to an improvement in the Faraday efficiency of DMF production, reaching 28%. Tong Wang et al explored the catalytic transfer hydrogenation of 5-HMF in the liquid phase for the delivery of DMF employing isopropanol as the hydrogen donor over a ternary CuxZnAl catalyst [56]. At 180 • C and 4 h of reaction, the DMF yield reached 91.7%.…”
Section: Non-precious Metalsmentioning
confidence: 99%
“…The analysis of pH effects on the conversion of HMF to various reduction products led to an improvement in the Faraday efficiency of DMF production, reaching 28%. Tong Wang et al explored the catalytic transfer hydrogenation of 5-HMF in the liquid phase for the delivery of DMF employing isopropanol as the hydrogen donor over a ternary CuxZnAl catalyst [56]. At 180 • C and 4 h of reaction, the DMF yield reached 91.7%.…”
Section: Non-precious Metalsmentioning
confidence: 99%
“…Only several Cu-, Ni-, and Ru-based , catalysts have been designed and applied for the HDO of HMF to DMF with isopropanol ( i -PrOH) as both the solvent and hydrogen donor. Particularly, inexpensive Cu-based catalysts are very attractive for this reaction because the full 3d valence band of Cu produces strong repulsion to the antibonding orbital of the furan ring, which could lead to the preferential adsorption of carbonyl group of HMF and minimize the hydrogenation/hydrogenolysis of a furan ring. However, the intrinsic catalytic activity of Cu for the C–O bond hydrogenolysis is low, resulting in a sluggish kinetic for the dehydroxylation reactions. , …”
Section: Introductionmentioning
confidence: 99%
“…37−39 However, the intrinsic catalytic activity of Cu for the C−O bond hydrogenolysis is low, resulting in a sluggish kinetic for the dehydroxylation reactions. 31,40 One of the efficient approach to promote the hydrogenolysis of C−O bond is to increase the content of Cu + species of the Cu-based catalysts because it can function as the Lewis acid sites to smooth the cleavage of C−O bond. 31,37,38 In addition, it has been reported that the Cu + species also serves as the active sites for the i-PrOH hydrogenation because of its better adsorption performance toward C�O and C−O bonds than Cu 0 species.…”
Section: Introductionmentioning
confidence: 99%